KARAKTERISTIK DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN MINUM OBAT PADA PASIEN SKIZOFRENIA - M. Ichsan Attafani Fillah; Lahargo Kembaren (Pusat riset dan Inovasi Nasional, 2022)
Mental disorders are one of the public health problems in Indonesia. In general, mental disorders are caused by psychological pressure both from outside the individual and from within the individual. Some of the things that cause this is the ignorance of the family and society about this mental disorder (Hawari, 2007). According to WHO or the World Health Organization (2002) states that the prevalence of mental health problems is currently quite high, 25% of the world's population has suffered from mental health problems, 1% of which are severe mental disorders. The potential for a person to be susceptible to mental disorders is indeed high, every time 450 million people around the world are affected by mental, nervous, and behavioral problems. One form of mental disorder that is found throughout the world is a severe mental disorder, namely Schizophrenia (Hawari, 2007). Schizophrenia comes from two words, namely schizo which means cracked or broken and phrenia which means soul. Thus, people who suffer from schizophrenic mental disorders are people who experience mental fractures or personality cracks. Schizophrenia can arise because of the integration between biological, psychosocial and environmental factors (Sinaga, 2007). In schizophrenic patients there is personal disintegration and personal division. Emotional and intellectual behavior becomes ambiguous (compound), and has serious disorders and has regression or total dementia. Schizophrenic patients escape from the reality of life and remain silent in their fantasy world (Kartono, 2010).